OPTIMIZATION OF THE QUALITATIVE CHARACTERISTICS OF HIGH-CARBON ROD - V. A. Lutsenko; V. V. Parusov; V. A. Matochkin; O. M. Kirilenko; E. V. Parusov; D. N. Andrianov (Литьë и металлургия)
The interrelation between thickness (mass) of cinder and microstructure parameters (pearlite dispersion and depth of decarbonized layer) in high-carbon rod after different regimes of TMO is established.